Negotiating the co-curation of an online community popular music archive. (31st December 2020) - Peter, Beate
Abstract : Co-curation has become a popular term in recent years. This article is concerned with the process, politics, issues and benefits of co-curation in the context of popular music heritage. It draws on literature concerned with popular music heritage as well as museum practices and the empirical (co)curation of exhibitions. Co-curation is discussed in relation to the Lapsed Clubber Audio Map, a publicly available digital community archive. Using the map and its memories as a case study, issues that were encountered during the creation of the map, are highlighted and some of the key theoretical and practical implications are reflected upon. Those are grouped together in terms of 'voicing heritage' and 'challenging narrative'. In order for heritage to be articulated, voices have to be identified, found and nurtured. The way in which co-curation then challenges a single chronological narrative is by facilitating different ways of remembering but also the invitation to contextualize these memories in different discourses.